META-ANALYSIS OF ENERGY EFFICIENCY IN EDUCATIONAL BUILDINGS - JACOB CHECA CERVANTES, DAVID (2024)
WITH THE HIGH CONSUMPTION OF ELECTRICAL ENERGY DUE TO THE PROGRESSIVE INCREASE IN DEMAND, IN THE RESIDENTIAL, COMMERCIAL AND INDUSTRIAL SECTORS, THE NEED ARISES TO OPT FOR STRATEGIES FOR ENERGY SAVING, WITH UNIVERSITY EDUCATIONAL BUILDINGS BEING A CASE THAT REQUIRES ANALYSIS IN LATIN AMERICA. THE PURPOSE OF THE FOLLOWING WORK IS TO COMPILE THE ALTERNATIVE SOLUTIONS OR MEASURES APPLIED BY UNIVERSITY EDUCATIONAL INSTITUTIONS IN LATIN AMERICA AND INDICATE WHICH ARE THE MAIN MEASURES TO ADOPT TO ACHIEVE ENERGY EFFICIENCY. THE PRISMA METHODOLOGY WAS USED FOR A SYSTEMATIC REVIEW. THE RESULTS INDICATE THAT ENERGY EFFICIENCY IS ACHIEVED THROUGH ACTIVE STRATEGIES WITH THE CHANGE IN ELECTRICAL EQUIPMENT TECHNOLOGY, ESPECIALLY LIGHTING AND AIR CONDITIONING, AS WELL AS PASSIVE STRATEGIES THROUGH ARCHITECTURAL DESIGN. IT IS CONCLUDED THAT IT IS NECESSARY TO IDENTIFY THE AREAS OF GREATEST ENERGY CONSUMPTION THROUGH A SYSTEM OF MEASUREMENTS, ENERGY INDICATORS AND AN INSTITUTIONAL ENERGY POLICY. IT IS ALSO VERIFIED THAT ENERGY EFFICIENCY CONTRIBUTES TO SAVINGS ON ELECTRICITY BILLS AND REDUCES THE CARBON FOOTPRINT. LIKEWISE, THE QUALITY OF LIGHTING IMPACTS THE ACADEMIC PERFORMANCE OF STUDENTS. © 2024 LATIN AMERICAN AND CARIBBEAN CONSORTIUM OF ENGINEERING INSTITUTIONS. ALL RIGHTS RESERVED.